TANTANGAN DAN PELUANG PEMBELAJARAN PENDIDIKAN ISLAM ??MODERAT ?DI LINGKUNGAN PESANTREN? MARHALAH RIBATH AL BATUL - Ita Fatmawati; Dini Nur Islami; Mohammad Makinuddin; Hani’atul Khoiroh (Jurnal Al-Fatih, 2025)
This study explores the challenges and opportunities in teaching moderate Islamic ?education at Mambaus Sholihin Islamic Boarding School, Suci Manyar Gresik. Using a ?qualitative descriptive approach with field research and the Miles and Huberman ?interactive analysis model, data were gathered through observation, interviews, and ?documentation. The results reveal three main challenges: students’ literal understanding ?of religious texts, the influence of social media on their religious views, and teachers’ ?difficulty in internalizing moderate values. However, the study also identifies promising ?opportunities, such as integrating moderation values into the Islamic curriculum, ?combining salaf and khalaf educational methods to strengthen moderation, and ?enhancing community engagement and da'wah activities aligned with the principles of ?rahmatan lil ‘alamin.